Pengaruh Ukuran Perusahaan, Struktur Modal, dan Good Corporate Governence terhadap Nilai Perusahaan Sektor Perbankan Tahun 2022-2024 - Anzalna Fadhila Rahmi; Mohammad Taufik Aziz; Mery Sukartini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explore and understand the impact of various internal corporate governance and financial structure variables on firm value, specifically within the context of the Indonesian banking sector. The variables examined include company size, capital structure, managerial ownership, institutional ownership, and the presence of independent commissioners. The study focuses on companies listed on the Indonesia Stock Exchange during the period from 2022 to 2024. A quantitative research approach was employed, using purposive sampling to select banking firms that met the criteria for analysis. The data were analyzed using multiple linear regression to determine the individual and simultaneous influence of each variable on firm value. The empirical findings reveal that company size does not have a significant effect on firm value, indicating that larger asset bases or broader operations are not necessarily associated with higher market valuation in the banking sector. Conversely, capital structure—reflected by the proportion of debt to equity—has a positive and significant effect, suggesting that leverage, when managed efficiently, enhances firm value. Meanwhile, managerial ownership does not show a notable contribution to firm value, implying that insider ownership may not always align with shareholder interests. On the other hand, institutional ownership exerts a positive and significant influence, indicating that the presence of large, professional investors can enhance oversight and value creation. Finally, the presence of independent commissioners does not significantly impact firm value. Overall, the results highlight that, although not all governance variables have a direct individual influence, the five variables studied jointly have a significant effect on firm value. These findings have implications for corporate governance practices and financial decision-making in the banking sector, especially in emerging markets such as Indonesia.